1989
DOI: 10.1128/jvi.63.12.5354-5363.1989
|View full text |Cite
|
Sign up to set email alerts
|

Construction of less neurovirulent polioviruses by introducing deletions into the 5' noncoding sequence of the genome

Abstract: Viral attenuation may be due to lowered efficiency of certain steps essential for viral multiplication. For the construction of less neurovirulent strains of poliovirus in vitro, we introduced deletions into the 5' noncoding sequence (742 nucleotides long) of the genomes of the Mahoney and Sabin 1 strains of poliovirus type 1 by using infectious cDNA clones of the virus strains. Plaque sizes shown by deletion mutants were used as a marker for rate of viral proliferation. Deletion mutants of both the strains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…5). Interestingly, engineered mutant polioviruses with similar extended deletions proved to be markedly attenuated in the monkey neurovirulence assay (328).…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…5). Interestingly, engineered mutant polioviruses with similar extended deletions proved to be markedly attenuated in the monkey neurovirulence assay (328).…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…This stretch may perform an essential function, as first suggested by Kuge and Nomoto (1987) on the basis of the assessment of the viability of poliovirus deletion mutants. This theory was further supported by experiments with modified poliovirus (Iizuka et al, 1989) and coxsackievirus B1 (Iizuka et al, 1990;A. Nomoto and N. Iizuka, personal communication) 5-UTRs.…”
Section: In Poliovirusmentioning
confidence: 84%
“…Specifically, the removal of nucleotides 630-726, 622-726, or 600-726 from the POliovirus type 1 (Sabin) genome does not alter such in uitro phenotypic properties of the virus as the plaque size or the time course of virus growth and development of cytopathic changes (see also Trono et al, 1988a). More extended deletions, 570-726 or 564-726, also produce viable progeny, but the mutant viruses exhibit a small-plaque (BPI phenotype due to their retarded growth rate (see also Iizuka et al, 1989). Assuming that phenotypic changes in this series of mutants are largely due to the altered function of the cis-acting translation control element (and we believe that this is a likely assumption), it could be concluded that the downstream border of this element should map between positions 564 and 600.…”
Section: In Poliovirusmentioning
confidence: 99%
See 2 more Smart Citations